"Encontros para a nova consciência" uma experiência religiosa da cultura pós-moderna? - Lain, Vanderlei Albino (2007)
The Convention for New Conscience occurs, during carnival period, in Campina Grande City (Paraíba - Brazil Northeast), since 1992, having become an attractive and intriguing event field, event that cannot be, currently, seen, found, easely, anywhere in the world. As we can observe this religious experience remarkable particularities, in such a great diversity, we are, therefore, enable to characterize it i.e. the abovementioned event as a kind, a sort of postmodern religious phenomenon. Studying the outstanding elements that are observed in this Movement, departing from the contemporaneous theorical contributions that reflect on the religious phenomenon, we will seek to present this experience as a religious liveliness meaningful space, within postmodern culture. If secularization and religious pluralism bestow some indications upon religious comportment in Modernity, the Convention for New Conscience characteristics, marked by the subjectivity that brings forth floating identities, they the event characteristics allow us evaluating a certain religiosity signs that take a plain shape in Post-modernity